ADVANTAGES OF DISTANCE LEARNING - Xaydarova Go'zalxon Xamdamjon qizi (Scholar Express Journals, 2022)
This article discusses the advantages, conveniences of distance learning, distance or regular classroom education, saving time and increasing the financial interest of distance education teachers, depending on the level of opportunity.
Keywords: Distance Learning; Preference; Information; Technology